The Comprehensive Analysis Speech Recognition System (International Journal of Innovative Research in Computer Science & Technology, 2021)
Automated computer speech detection has  been a goal of research for almost four decades. The idea  underlying the development of a voice recognition system  is that it is beneficial for people to communicate with a  computer, robot or another device via speech. Researchers  want to utilize people's voices in an integrated environment  to provide customers comfort and flexibility in today's era.  Speech recognition is dependent on the input voice signal.  It enables the computer to transform the voice signal to text  or instructions using the technique of recognition and  understanding. This article describes the fundamental  concept of speaking recognition, types of voice recognition,  difficulties with speech recognition, several ways to gather  characteristics, and different pattern-matching algorithms to  identify the different speakers. The technology of voice  recognition is inspired by a wide vocabulary automated  speech recognition system which allows language independent operation and continuous speaking in a foreign  language.
Keywords: ANN; Feature Extraction; Markov Model; Speech Recognition; Voice Recognition